Barnstorming to Heaven : Syd Pollock and His Great Black Teams - Pollock, Alan J. (Book collections on Project MUSE., 2012)
"A rare insider's perspective on baseball's great barnstorming age. The Indianapolis Clowns were a black touring baseball team that featured an entertaining mix of comedy, showmanship, and skill. Sometimes referred to as the Harlem Globetrotters of baseball--though many of the Globetrotters' routines were borrowed directly from the Clowns--they captured the affection of Americans of all ethnicities and classes. Alan Pollock's father, Syd, owned the Clowns, as well as a series of black barnstorming teams that crisscrossed the country from the late 1920s until the mid-1960s. They played every venue imaginable, from little league fields to Yankee Stadium, and toured the South, the Northeast, the Midwest, the Canadian Rockies, the Dakotas, the Southwest, the Far West--anywhere there was a crowd willing to shell out a few dollars for an unforgettable evening. Alan grew up around the team and describes in vivid detail the comedy routines of Richard "King Tut" King, "Spec Bebob" Bell, Reece "Goose" Tatum; the "warpaint" and outlandish costumes worn by players in the early days; and the crowd-pleasing displays of amazing skill known as pepperball and shadowball. These men were entertainers, but they were also among the most gifted athletes of their day, making a living in sports the only way a black man could. They played to win. More than just a baseball story, these recollections tell the story of great societal changes in America from the roaring twenties, through the years of the Great Depression and World War II, and into the Civil Rights era."--